2009
DOI: 10.2337/dc09-s087
|View full text |Cite
|
Sign up to set email alerts
|

National Standards for Diabetes Self-Management Education

Abstract: Diabetes self-management education (DSME) is a critical element of care for all people with diabetes and is necessary in order to improve patient outcomes. The National Standards for DSME are designed to define quality diabetes self-management education and to assist diabetes educators in a variety of settings to provide evidence-based education. Because of the dynamic nature of health care and diabetes-related research, these Standards are reviewed and revised approximately every 5 years by key organizations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 557 publications
(132 citation statements)
references
References 134 publications
(98 reference statements)
1
124
0
3
Order By: Relevance
“…Recent studies suggest that any type of education for nutrition has resulted in reduced hospitalization [18]. In fact, the guidelines for diabetes self-management education were developed by a recent task force to identify ten detailed standards for diabetes self-management education [19].…”
Section: Risk Factors For All-cause Mortality In Dm Patientsmentioning
confidence: 99%
“…Recent studies suggest that any type of education for nutrition has resulted in reduced hospitalization [18]. In fact, the guidelines for diabetes self-management education were developed by a recent task force to identify ten detailed standards for diabetes self-management education [19].…”
Section: Risk Factors For All-cause Mortality In Dm Patientsmentioning
confidence: 99%
“…This is particularly true for persons with diabetes. Research evidence shows that patient education has a positive effect on patient outcomes [12,13] . Ulrich et al [14] surmised that the contents of diabetes patient education are Meal, Move, Medication, Meter and More.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes self-management education (DSME) is a critical element of diabetes care (Funnell et al 2009). A vast number of studies have shown that DSME (Ellis et al 2004;Norris, Engelgau & Narayan 2001;Norris et al 2002) including nutrition education (NE) (Pastors et al 2002;Shabbidar, Fathi & Shirazifard 2006) significantly improves health outcomes.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…A comprehensive needs assessment is thus crucial (Muchiri, Gericke & Rheeder 2009;Glazier et al 2006Brown et al 2002. Determination of the education needs of the target population(s) is one of the DSME standards stipulated by organisations dealing with diabetes (International Diabetes Federation 2009;Funnell et al 2009). …”
Section: Introduction Backgroundmentioning
confidence: 99%